2014
DOI: 10.1111/jsm.12246
|View full text |Cite
|
Sign up to set email alerts
|

Remitted Male Schizophrenia Patients with Sexual Dysfunction

Abstract: Introduction Despite the high prevalence of sexual dysfunction among male schizophrenia patients, there is still a paucity of research on this area. Aims The study aims to determine the prevalence of sexual dysfunction and any association between male patients with schizophrenia in remission and the sociodemographic profile, medication, depression, anxiety, psychopathology of illness, body mass index, and waist circumference.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
1
10
1
Order By: Relevance
“…The prevalence of sexual dysfunction was higher in females (82.7%), than in males (64.5%), which is consistent with findings reported in other studies (female 45–80% and male 30–80%) [1, 14, 17, 43]. Compared to our study conducted in the city areas of Guangdong using the same assessment tools which showed a prevalence of sexual dysfunction of 80.6% in females and 60.7% in males [44], the prevalence in the rural areas appear slightly higher than in city areas.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The prevalence of sexual dysfunction was higher in females (82.7%), than in males (64.5%), which is consistent with findings reported in other studies (female 45–80% and male 30–80%) [1, 14, 17, 43]. Compared to our study conducted in the city areas of Guangdong using the same assessment tools which showed a prevalence of sexual dysfunction of 80.6% in females and 60.7% in males [44], the prevalence in the rural areas appear slightly higher than in city areas.…”
Section: Discussionsupporting
confidence: 91%
“…According to a meta analysis, the prevalence of sexual dysfunction reported in Asia countries was lower than western counties [15]. Further, clinicians themselves may be conservative in enquiring about sexual concerns or consider sexual-related complains as insignificant in schizophrenia patients as compared to positive psychotic symptoms [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When it was possible, the authors were contacted by email in case of missing data. Four teams were contacted (Byerly et al, 2006;Konarzewska et al, 2009;Mahmoud et al, 2012aMahmoud et al, , 2011aOng et al, 2014a). but none of them answered.…”
Section: Methodsmentioning
confidence: 99%
“…Although there is a paucity of research into this area it has also been suggested that loss of interest in sex in people with schizophrenia is associated with advancing age, female gender, cardiovascular medication, negative symptoms and lower sexual self-efficacy (self-confidence and self-control in sexual experiences) (Bianco 2019). It is not clear whether treatment of the psychotic disorder confers an improvement in dysfunctions: a study of men with schizophrenia in remission still showed high levels of dysfunction (between 78.4 and 97.1%) across five domains of sexual functioning (Kheng Yee 2014). Another aspect of sexuality studied in schizophrenia is risky sexual behaviour, which refers to unprotected sex with risk of unwanted/unintended pregnancy and transmission of sexual diseases.…”
Section: Mental Illness and Sexual Dysfunctionmentioning
confidence: 99%